2022
DOI: 10.1108/qmr-08-2021-0100
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical environment design on the dimensions of emotional well-being: a qualitative study from the perspective of design and retail managers

Abstract: Purpose This study aims to use place identity theory to examine the concept of physical environment design (PED) and its effects on consumers’ emotional well-being (EWB) dimensions such as sensorium, behaviour and happiness. Design/methodology/approach The authors used a qualitative approach. Thirty interviews were conducted among participants drawn from the city of London, which is one of the flourishing and world’s most famous international trade centre, providing paramount access to the global market. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 109 publications
(146 reference statements)
0
2
0
1
Order By: Relevance
“…Analysis showed that only limited moderating effects of these characteristics were present, but overall the associations between PED and EWB were independent of age and gender. However, all the consumers had their own personalised store experiences on the basis of their understanding and social background (Khaneja et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis showed that only limited moderating effects of these characteristics were present, but overall the associations between PED and EWB were independent of age and gender. However, all the consumers had their own personalised store experiences on the basis of their understanding and social background (Khaneja et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The current paper explains that EWB is highly influenced by PED of the retail stores. Culminating on the importance of EWB in retail stores, with articulation on the significance for managers of acknowledging consumers’ emotional responses to certain behaviours (Khaneja et al , 2022), this study provides a rubric with new benchmarks that customers might perceive during their visit to the retail stores (Pantano et al , 2022). The work contributes to the academic body of knowledge on PED by justifying its dimensions: ambience, artefacts and spatiality.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…En [16] estudio utilizó la teoría de la identidad del lugar para del entorno físico (PED) y sus efectos en las dimensiones del bienestar emocional de los consumidores (EWB), como el sensorio, el comportamiento y la felicidad. Los autores utilizaron un enfoque cualitativo, se realizó treinta entrevistas entre los participantes de la ciudad de Londres y los datos fueron analizados mediante análisis temático.…”
Section: B Actividades Logística Del Canal De Distribuciónunclassified